2022
DOI: 10.1055/a-1876-2423
|View full text |Cite
|
Sign up to set email alerts
|

Gesundheitliche Lage in der Ukraine vor Kriegsbeginn und ihre Relevanz für die Versorgung ukrainischer Geflüchteter in Deutschland: Literaturdurchsicht, Risikoanalyse und Prioritätensetzung

Abstract: Zusammenfassung Hintergrund Die gesundheitlichen Bedarfe Geflüchteter ergeben sich nicht nur aus Expositionen während Krieg und Flucht. Auch Determinanten aus dem Lebenslauf und etabliertes Gesundheitsverhalten spielen eine Rolle. Wir untersuchten daher die gesundheitliche Lage in der Ukraine vor der russischen Invasion 2022 und ihre Relevanz für die Versorgung ukrainischer Geflüchteter in Deutschland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
5
0
5
Order By: Relevance
“…Dies wird oft als problematisch und zeitaufwändig bezeichnet. Ein universeller Zugang zu medizinischen Dolmetschenden sollte ermöglicht werden, wie bereits in Kanada [ 17 ] und Deutschland [ 18 ] gefordert. Unterstützung bieten befristete Angebote wie die telefonische Dolmetsch-Nothilfe ( https://dolmetsch-nothilfe.org ).…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Dies wird oft als problematisch und zeitaufwändig bezeichnet. Ein universeller Zugang zu medizinischen Dolmetschenden sollte ermöglicht werden, wie bereits in Kanada [ 17 ] und Deutschland [ 18 ] gefordert. Unterstützung bieten befristete Angebote wie die telefonische Dolmetsch-Nothilfe ( https://dolmetsch-nothilfe.org ).…”
Section: Diskussionunclassified
“…Blutenop et al. [ 18 ] fordern daher, niedrigschwellige psychosoziale inklusive sozialpädagogische Angebote initial in Sammelunterkünften und Erstaufnahmeeinrichtungen zu erwägen. Murphy et al.…”
Section: Diskussionunclassified
“…For this to occur, future research should focus on interventional studies further investigating the effects of CBPR interventions to achieve level 1 evidence. Further studies should also assess whether the observed effects can be transferred to other socially disadvantaged groups [e.g., migrant groups who have more recently arrived in Germany, such as Ukrainian refugees ( 65 )].…”
Section: Discussionmentioning
confidence: 99%
“…This specific group deserves special attention from health professionals, as they have different needs and vulnerabilities with regard to integration and the safeguarding of human rights ( 1 ) . Health professionals are ethically obligated to prepare a response to public health and health-related issues arising from the refugee movement ( 2 ) .…”
Section: Introductionmentioning
confidence: 99%
“…There are currently millions of forcibly displaced people in the world. Among them, a large number are refugees due to civil wars in Syria, Libya, Afghanistan, Iraq and South Sudan, and, more recently, due to the war in Ukraine (1)(2)(3) . Indeed, refugees' current situation in Europe is the greatest since the Second World War (2) .…”
Section: Introductionmentioning
confidence: 99%